2018
DOI: 10.1108/jtf-05-2018-0032
|View full text |Cite
|
Sign up to set email alerts
|

Back to the future with IATA NDC? Critical turning points in the history of airline distribution

Abstract: Purpose -The International Air Transport Association (IATA) New Distribution Capability (NDC) standard aims at modernising the airline distribution landscape. It has supported the spread of Direct Connects by providing a common standard for linking airlines to travel agencies. The purpose of this paper is to analyse the historical development of airline distribution and to derive implications for the future. Design/methodology/approach -This paper follows the approach of Yeoman and McMahon-Beattie (2017) in pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
0
7
0
1
Order By: Relevance
“…Furthermore, the study noted that the IoT-based CRM enhanced the analytic capabilities of airlines, enabled them to spot changes in consumer purchasing patterns, and allowed them to provide individualized services to customers to retain them. Bingemer (2018) undertook a literature reviewbased study to investigate the historical evolution of airlines' distribution capabilities. The study reports IoT as the most influential technological driver of airline companies' distribution capabilities in modern times.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the study noted that the IoT-based CRM enhanced the analytic capabilities of airlines, enabled them to spot changes in consumer purchasing patterns, and allowed them to provide individualized services to customers to retain them. Bingemer (2018) undertook a literature reviewbased study to investigate the historical evolution of airlines' distribution capabilities. The study reports IoT as the most influential technological driver of airline companies' distribution capabilities in modern times.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Prior research in the airline industry has shown several advantages of using IoT-based CRM technology. IoT-based CRM enables airlines to provide customized services to passengers at a reasonable cost (Hammoud et al, 2018;He, 2020;Tang and Zhang, 2022), improve the availability of services (Keivanpour and Kadi, 2019;Pillai and Devrakhyani, 2020) and customer experience (Bingemer, 2018;Sharma et al, 2021;Ordóñez et al, 2020). However, there is a shortage of research studies that portray the significance of IoT-based CRM in leading to customer satisfaction and loyalty in the airline industry.…”
Section: Introductionmentioning
confidence: 99%
“…Amadeus, Sabre, and Travelport, dominated the airline distribution landscape for a long time. But all of this changed with the introduction of New Distribution Capability (NDC) by Direct Connect and International Air Transport Association (IATA) (Bingemer, 2018).…”
Section: Gds To New Distribution Capability (Ndc)mentioning
confidence: 99%
“…However, some of the individual airlines and hotel chains are trying to sell their products directly to their customers by overlooking GDS (Pan, 2015). Airlines felt that the dependence on GDS was not necessary for full-cost carriers (Bingemer, 2018). The two key factors which were behind the creation of NDC, namely Rich content and GDS-centric distribution as the existing system is complex (Eisner (2019).…”
Section: Review Of Literaturementioning
confidence: 99%
“…, 2007). Her birinin güçlü bölgeleri değişkenlik göstermekle birlikte pazar paylarına ilişkin tam bir bilgi bulunmamakta, dünyada bu üç sistem üzerinden büyük bir işlem hacmi gerçekleşmektedir (Bingemer, 2018). Ancak üç dağıtım sisteminin sağladığı gelir düzeyi Covid-19 öncesinde yaklaşık 14 Milyar Amerikan Doları'dır (Statista).…”
Section: Introductionunclassified